State management institutions for import-export procedures in Vietnam - Thinh, Nguyen Diep (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Drawing on Institutional Theory and Transaction Cost Economics, this study investigates how procedural inefficiencies and bureaucratic barriers within state management institutions affect the competitiveness of businesses in Vietnam’s import-export sector. Through a mixed-methods approach combining qualitative interviews and quantitative surveys, the research examines the relationships between institutional inefficiencies, transaction costs, and business performance. The findings reveal significant negative impacts: procedural inefficiencies reduce business competitiveness (β = -0.45, p < 0.01), while bureaucratic barriers increase operational costs (β = 0.39, p < 0.05), particularly affecting SMEs. These challenges manifest through lengthy customs clearance processes (averaging 20 hours delay), excessive documentation requirements (12 documents versus the regional standard of 7), and frequent regulatory changes. Digital solutions demonstrate significant moderating effects (β = 0.28, p < 0.05), potentially reducing negative impacts by up to 20%. Based on these findings, the study recommends expanding the National Single Window system, implementing standardized documentation templates, enhancing digital infrastructure, and establishing clear performance metrics. These evidence-based reforms are essential for improving Vietnam’s trade competitiveness and creating a more efficient, transparent business environment in the import-export sector.